Copper-mediated oxidative C−H/N−H activations with alkynes by removable hydrazides - Xiong, Feng; Li, Bo; Yang, Chenrui; Zou, Liang; Ma, Wenbo; Gu, Linghui; Mei, Ruhuai; Ackermann, Lutz (Beilstein Journal of Organic Chemistry, 2021)
The efficient copper-mediated oxidative C–H alkynylation of benzhydrazides was accomplished with terminal alkynes. Thus, a heteroaromatic removable N-2-pyridylhydrazide allowed for domino C–H/N–H functionalization. The approach featured remarkable functional group compatibility and ample substrate scope. Thereby, highly functionalized aromatic and heteroaromatic isoindolin-1-ones were accessed with high efficacy with rate-limiting C–H cleavage.
Keywords: benzhydrazides; copper; 3-methyleneisoindolin-1-one; removable directing group

(untitled) - Gandeepan, P.; Finger, L. H.; Meyer, T. H.; Ackermann, L. (Chem. Soc. Rev., 2020)

(untitled) - Ellman, J. A.; Ackermann, L.; Shi, B.-F. (J. Org. Chem., 2019)

(untitled) - Yi, H.; Zhang, G.; Wang, H.; Huang, Z.; Wang, J.; Singh, A. K.; Lei, A. (Chem. Rev., 2017)

(untitled) - Wei, Y.; Hu, P.; Zhang, M.; Su, W. (Chem. Rev., 2017)

(untitled) - Rao, W.-H.; Shi, B.-F. (Org. Chem. Front., 2016)

(untitled) - Zheng, Q.-Z.; Jiao, N. (Chem. Soc. Rev., 2016)

(untitled) - Wencel-Delord, J.; Glorius, F. (Nat. Chem., 2013)

(untitled) - Rouquet, G.; Chatani, N. (Angew. Chem., Int. Ed., 2013)

(untitled) - Engle, K. M.; Mei, T.-S.; Wasa, M.; Yu, J.-Q. (Acc. Chem. Res., 2012)

(untitled) - Yamaguchi, J.; Yamaguchi, A. D.; Itami, K. (Angew. Chem., Int. Ed., 2012)

(untitled) - Li, C.-J. (Acc. Chem. Res., 2009)

(untitled) - Chen, X.; Hao, X.-S.; Goodhue, C. E.; Yu, J.-Q. (J. Am. Chem. Soc., 2006)

(untitled) - Uemura, T.; Imoto, S.; Chatani, N. (Chem. Lett., 2006)

(untitled) - Kim, H.; Heo, J.; Kim, J.; Baik, M.-H.; Chang, S. (J. Am. Chem. Soc., 2018)

(untitled) - Takamatsu, K.; Hirano, K.; Miura, M. (Angew. Chem., Int. Ed., 2017)

(untitled) - Wang, S.; Guo, R.; Wang, G.; Chen, S.-Y.; Yu, X.-Q. (Chem. Commun., 2014)

(untitled) - Nishino, M.; Hirano, K.; Satoh, T.; Miura, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kim, J.; Kim, H.; Chang, S. (Org. Lett., 2012)

(untitled) - Zhang, L.; Liu, Z.; Li, H.; Fang, G.; Barry, B.-D.; Belay, T. A.; Bi, X.; Liu, Q. (Org. Lett., 2011)

(untitled) - Lamblin, M.; Couture, A.; Deniau, E.; Grandclaudon, P. (Org. Biomol. Chem., 2007)

(untitled) - Rys, V.; Couture, A.; Deniau, E.; Grandclaudon, P. (Tetrahedron, 2003)

(untitled) - Chia, Y.-C.; Chang, F.-R.; Teng, C.-M.; Wu, Y.-C. (J. Nat. Prod., 2000)

(untitled) - Blaskó, G.; Gula, D. J.; Shamma, M. (J. Nat. Prod., 1982)

(untitled) - Botero Cid, H. M.; Tränkle, C.; Baumann, K.; Pick, R.; Mies-Klomfass, E.; Kostenis, E.; Mohr, K.; Holzgrabe, U. (J. Med. Chem., 2000)

(untitled) - Dong, J.; Wang, F.; You, J. (Org. Lett., 2014)

(untitled) - Zhang, Y.; Wang, Q.; Yu, H.; Huang, Y. (Org. Biomol. Chem., 2014)

(untitled) - Zhu, W.; Wang, B.; Zhou, S.; Liu, H. (Beilstein J. Org. Chem., 2015)

(untitled) - Lee, W.-C. C.; Wang, W.; Li, J. J. (J. Org. Chem., 2018)

(untitled) - Zaitsev, V. G.; Shabashov, D.; Daugulis, O. (J. Am. Chem. Soc., 2005)

(untitled) - Lee, W.-C. C.; Shen, Y.; Gutierrez, D. A.; Li, J. J. (Org. Lett., 2016)

(untitled) - Zhang, L.-B.; Hao, X.-Q.; Liu, Z.-J.; Zheng, X.-X.; Zhang, S.-K.; Niu, J.-L.; Song, M.-P. (Angew. Chem., Int. Ed., 2015)

(untitled) - Zheng, X.-X.; Du, C.; Zhao, X.-M.; Zhu, X.; Suo, J.-F.; Hao, X.-Q.; Niu, J.-L.; Song, M.-P. (J. Org. Chem., 2016)

(untitled) - Hao, X.-Q.; Du, C.; Zhu, X.; Li, P.-X.; Zhang, J.-H.; Niu, J.-L.; Song, M.-P. (Org. Lett., 2016)

(untitled) - Tian, C.; Dhawa, U.; Scheremetjew, A.; Ackermann, L. (ACS Catal., 2019)

(untitled) - Fitzgerald, L. S.; O'Duill, M. L. (Chem. – Eur. J., 2021)

(untitled) - Zhai, S.; Qiu, S.; Chen, X.; Wu, J.; Zhao, H.; Tao, C.; Li, Y.; Cheng, B.; Wang, H.; Zhai, H. (Chem. Commun., 2018)

(untitled) - Zhao, H.; Wang, T.; Qing, Z.; Zhai, H. (Chem. Commun., 2020)

(untitled) - Zhao, H.; Shao, X.; Wang, T.; Zhai, S.; Qiu, S.; Tao, C.; Wang, H.; Zhai, H. (Chem. Commun., 2018)

(untitled) - Zhai, S.; Qiu, S.; Chen, X.; Tao, C.; Li, Y.; Cheng, B.; Wang, H.; Zhai, H. (ACS Catal., 2018)

(untitled) - Qiu, S.; Zhai, S.; Wang, H.; Tao, C.; Zhao, H.; Zhai, H. (Adv. Synth. Catal., 2018)

(untitled) - Mei, R.; Fang, X.; He, L.; Sun, J.; Zou, L.; Ma, W.; Ackermann, L. (Chem. Commun., 2020)

(untitled) - Sau, S. C.; Mei, R.; Struwe, J.; Ackermann, L. (ChemSusChem, 2019)

(untitled) - Mei, R.; Ma, W.; Zhang, Y.; Guo, X.; Ackermann, L. (Org. Lett., 2019)

(untitled) - Mei, R.; Sauermann, N.; Oliveira, J. C. A.; Ackermann, L. (J. Am. Chem. Soc., 2018)

(untitled) - Mei, R.; Dhawa, U.; Samanta, R. C.; Ma, W.; Wencel‐Delord, J.; Ackermann, L. (ChemSusChem, 2020)

(untitled) - Sauermann, N.; Mei, R.; Ackermann, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - Mei, R.; Wang, H.; Warratz, S.; Macgregor, S. A.; Ackermann, L. (Chem. – Eur. J., 2016)

(untitled) - Mei, R.; Loup, J.; Ackermann, L. (ACS Catal., 2016)

(untitled) - Mei, R.; Ackermann, L. (Adv. Synth. Catal., 2016)

(untitled) - Ackermann, L. (Chem. Rev., 2011)